The 2013 Revised Curriculum and Independent Curriculum Implementation in English Classes - Prameswari, Taqiya Nabila; Fahriany, Fahriany; Nahartini, Desi (Journal of English Language and Education, 2023)
The purpose of this study is to learn more about the implementation of the 2013 revised curriculum and the independent curriculum in two Jakarta senior high schools. It also intends to ascertain teachers' opinions of the two curricula, as well as the difficulties and solutions they faced while putting the two curricula into practice. The government released an independent curriculum in 2019 to replace the 2013 revised curriculum, which was altered due to the pandemic and deteriorating literacy abilities of students. This new curriculum is being tested in a number of schools for the 2022–2023 academic year. Each school used both curricula, with four teachers from the two distinct schools participating. Qualitative approaches were employed in this study, including document analysis, observations, and interviews. The outcomes demonstrated that the tests and learning activities in both curricula were implemented precisely. The variations seen in the assignments and resources in the separate curriculum.  Making learning objectives from learning outcomes in the independent curriculum is another challenge that teachers face. Teachers, however, had a favorable opinion of the 2013 revised curriculum and projects. Based on the study's findings, it is still difficult to determine learning because of the varied skill levels of the students and the ineffective application of the independent curriculum. The objectives of the new curriculum must therefore be met by teacher preparation, particularly when it is implemented fully in 2024.